RESIDU PESTISIDA ALDRIN DAN DIELDRIN PADA SAMPEL TANAH DAN AIR DI DESA SRIGADING KECAMATAN SANDEN KABUPATEN BANTUL - Narwanti, Iin; Sugiharto, Eko; Anwar, Chairil (Pharmaciana, 2013)
Aldrin and dieldrin pesticide residue in soil and water samples from Srigading Village, Sanden District,Bantul Regency has been investigated. The purpose of this study were to analyze, identificate and evaluatepyrethroid pesticide residues in soil and water samples. Soil sample was extracted using shaker with acetonesolvent. Water samples was extracted using separator funnel with 15% (v/v) dichloromethane/n-hexanesolvent.Clean-up was couducted using chromatography column using florisil and determination of pesticideresidue in the samples was carried out by gas chromatography apparatus equipped with electron capture detector(GC-ECD). The result showed that pesticide residues in soil sample in the range level: aldrin (4,8-64,8 ppb) anddieldrin (not detected-6,0 ppb). In water sample pesticide residues in the range level: aldrin (not detected-1,0 ppb)dan dieldrin (-not detected1,2 ppb). The quality or water sample taken from onion field is laid under the standardof water that has been settled.